Facility Security Measures at Ujung Jabung Port: a Review in Terms of The International Ship and Port Facility Security Code - Farisi, Mochammad; Putra, Akbar Kurnia; Ardianto, Budi; Harahap, Rahayu Repindowaty (UI Scholars Hub, 2020)
Ujung Jabung is a region located in the District of Sadu at Tanjung Jabung Regency, Jambi Province, Indonesia. The area strategically lies in the Indonesian Archipelagic Sea Lane 1 (ALKI 1), which is the international trading and shipping lane. It brings about an excellent opportunity for economic development in Jambi Province. With this in mind, the Government of Jambi develops the region into a strategic area that includes Ujung Jabung Port. Based on the 2011-2031 Region’s Spatial Plan (RTRW) of East Tanjung Jabung Regency, the regency designed it to be the main port with the name of Samudera Ujung Jabung Port. The international shipping routes at the port are Ujung Jabung-West Asia-East Europe and Ujung Jabung-Southeast Asia-East Asia. Due to its international nature, the construction of Samudera Ujung Jabung Port should follow the international measures on the security of the port, shipping, and facility. As a Member of the International Maritime Organization (IMO), Indonesia is subject to international law. It ratifies the United Nations Convention on Safety on Life at Sea (SOLAS) 1974 and the auxiliary instrument of International Ships and Port Facility Code (ISPS Code). Accordingly, the construction of Samudera Ujung Jabung Port should comply with the international safety standard as written in the ISPS Code.